PELAYANAN KESEHATAN DI PUSKESMAS ILU KABUPATEN PUNCAK JAYA PROVINSI PAPUA - KOGOYA, KARUNGGA; RUMAPEA, PATAR; DENGO, SALMIN (Sam Ratulangi University, 2018)
the purpose of this research is to know the health service in Puskesmas Ilu Puncak Jaya Regency PapuaProvince.The concept used is four dimensions of excellent public service namely the speed of service, service accuracy,service accuracy, and service quality. This research uses quantitative method. The research informants werefour officers / employees of Ilu Puskesmas and four community members. Data were collected using interviewguidelines, while analytical techniques used were interactive model analysis from Miles and Hubernann. Basedon the results of data analysis, the conclusions are drawn: (1) The speed of service is still low. The communityof service users often waits for hours to get health care because service personnel are often late for hours towork, often not even working for days. (2) The accuracy of service is still low. The timing of service deliveryand completion is always inappropriate. The service procedure does not work properly because the officer /employee is not disciplined and lacks responsibility in providing service well. (3) Accuracy of service is still low.Health services are made improvised by the condition of facilities and equipment that are less / inadequate.There is no guaranteed assurance of service to the public or the patient. (4) Quality of service is still low. Theprocess of the implementation of the service has not gone well and has not been in accordance with the needsof the community.Based on the conclusions of the research results are recommended: (1) Puskesmas staff must be disciplinedin terms of working time (hours of work-going and attendance on every working day). (2) Need to improvediscipline and responsibilities of employees / officers. (3) It is necessary to increase the commitment andcompetence of officers / officers. (4) Need improvement of facilities and equipments and provision of adequateservice facility, improvement of officer / employee competence, and improvement of motivation throughimprovement of welfare of officer / officer.Keywords: Health Service Puskesmas